Silver nanoparticles sintering at low temperature on a copper substrate: In situ characterization under inert atmosphere and air - Sopousek J.; Bursik J.; Zalesak J.; Pesina Z. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Silver nanoparticles (Ag-NPs) were prepared by wet synthesis. The Ag-NPs suspension and the copper substrate plate were used for a preparation of substrate-nanoparticle-substrate samples. The sandwich like samples Cu/Ag/Cu were prepared and investigated in-situ at the isothermal external conditions (IEC) and inside apparatus for simultaneous thermal analysis STA409 (DSC). The in-situ results of the electrical resistance were recorded during the Cu/Ag/Cu (IEC) sample preparation and heat treatment. Thermal effects of the Ag-NPs sintering between copper substrates were measured by differential scanning calorimetry (DSC) under different atmospheres. The prepared Cu/Ag/Cu sandwich samples were characterised by means of both optical and electron microscopy. The process of the low temperature sintering inside calorimeter of the Ag-NPs was monitored using both thermogravimetry (TG) and DSC technique under inert gas and under synthetic air. The exothermic heat effect of nanosilver sintering was evaluated.